Pengaruh Model Pembelajaran Project Based Learning Berbantuan Media Prezi terhadap Keterampilan Menulis Teks Biografi Siswa Kelas X SMAN 1 Batipuh - Ardian, Miranda; R, Syahrul (AHKAM, 2024)
One important aspect of Indonesian language learning is the development of writing skills. Writing skills can be taught through Indonesian language learning because of the independent curriculum, especially on biography texts. Efforts to improve student writing learning outcomes by choosing a learning model in the form of a project-based learning model . The purpose of this study was to analyze the effect of the project-based learning model on the writing skills of biographical texts of SMA Negeri 1 Batipuh class students. The method used in this research is quantitative method by using quasi experimental research. The sample used was selected based on purposive sampling technique. The sample in this study amounted to 60 students. The data in this study are in the form of scores converted from scores based on two tests of biography text writing skills on the sample.Based on data analysis and discussion, it can be concluded three things First, students' biography text writing skills without using the project-based learning model obtained an average of 74.87 with LDC qualifications (More than Sufficient) Second, students' biography text writing skills using the project-based learning model obtained an average of 83.47 with Good (B) qualifications. Third, the use of project-based learning model affects the biography text writing skills of students in class X SMA Negeri 1 Batipuh with a level of 95%.